Efficacy and safety of combination therapy with prednisolone and oral tacrolimus for progressive interstitial pneumonia with systemic sclerosis: A retrospective study. Issue 6 (2nd November 2018) - Konma, Junichi; Kotani, Takuya; Shoda, Takeshi; Suzuka, Takayasu; Fujiki, Youhei; Nagai, Koji; Hata, Kenichiro; Yoshida, Shuzo; Takeuchi, Tohru; Makino, Shigeki; Arawaka, Shigeki
Abstract: Objectives: We retrospectively investigated efficacy and safety of combination therapy with prednisolone (PSL) and tacrolimus (TAC) for progressive interstitial pneumonitis with systemic sclerosis (SSc-PIP). Methods: We studied 11 patients with SSc-PIP who received combination therapy with PSL (0.5 mg/kg/d) and TAC (3 mg/d). Results: Baseline Hugh-Jones grades were I, II, III, and IV in 2, 6, 2, and 1 patients, respectively. Krebs von den Lungen-6 (KL-6) values were elevated to 914 (range 300–2614) U/mL. % Diffusing capacity of carbon monoxide (%DLco) remarkably decreased to 47.4 (range 9.7–64.4) %. All patients were alive at 1 year after therapy. In response to treatment, interstitial pneumonia (IP) improved in three patients, stable in seven patients, and deteriorated in one patient. Total ground-glass opacity (GGO) score improved ( p  = .005). No significant changes occurred in values of KL-6, % forced vital capacity (%FVC), and %DLco. Presently, all seven patients who could be followed up were alive. IP improved in three patients and stable in four patients. Total GGO score improved ( p  = .016). KL-6, %FVC, and %DLco did not change. Mild cytomegalovirus or herpes zoster infection occurred in two patients. Grade I renal injuries were observed in three and one patient at 1 year and present, respectively. Conclusion: Combination therapy with PSL and TAC appeared to be well tolerated and effective in suppressing the disease activity of SSc-PIP.